Spiritualita Colina H. van Eeckhouta a Church of Ra: dualita a bolest - Nenadalová, Jana (Sacra, 2019)
Colin H. van Eeckhout is a Belgian singer, songwriter and one of the founding members of Belgian music collective Church of Ra. I focus closely on his postmetal band Amenra, through whose music, symbolic and ritual performances - like suspension and other types of flesh hook insertions - Colin wants to convey his own spirituality and experience of existential pain. Duality of life and existence of immanent life's pain is by him and the other members of CoR taken as a serious and grave spiritual theme, although it can be used as potential for process of healing through catharsis (both for the band members and for their audience). Moreover, I focus on Colin's own personal spirituality with links to its broader connotations in context of CoR's music, art, and performances - especially the extreme rituals. I will also briefly introduce and analyze so called "modern primitive movement", through its philosophy became bodily pain sacred and extreme rituals are taken (beside else) as means to transcendental state.